Intensified tuberculosis treatment to reduce the mortality of HIV-infected and uninfected patients with tuberculosis meningitis (INTENSE-TBM): study protocol for a phase III randomized controlled trial - Maitre, Thomas; Bonnet, Maryline; Calmy, Alexandra; Raberahona, Mihaja; Rakotoarivelo, Rivonirina Andry; Rakotosamimanana, Niaina; Ambrosioni, Juan; Miró, José M.; Debeaudrap, Pierre; Muzoora, Conrad; Davis, Angharad; Meintjes, Graeme; et al. (Current controlled trials in cardiovascular medicine, 2022)
Background Tuberculous meningitis (TBM) is the most lethal and disabling form of tuberculosis (TB), particularly in sub-Saharan Africa. Current anti-TB treatment is poorly effective since TBM mortality reaches 40% in HIV-negative patients and up to 70% in HIV-co-infected patients. To reduce TBM-induced morbidity and mortality, the INTENSE-TBM trial evaluates two interventions in both HIV-infected and uninfected patients: an anti-TB treatment intensification using oral high-dose rifampicin (35 mg/kg daily) and linezolid (1200 mg daily and then 600 mg daily) during the first 8 weeks of the anti-TB treatment and the use of adjunctive aspirin (200 mg daily). Methods This is a randomized controlled, phase III, multicenter, 2 × 2 factorial plan superiority trial. The trial has four arms, combining the two experimental treatments (intensified TBM regimen and aspirin) with the two reference treatments (WHO standard TB treatment and placebo), and is open-label for anti-TB treatment and double-blind placebo-controlled for aspirin treatment. This trial is conducted in adults or adolescents of age ≥15 years with TBM defined as “definite,” “probable,” or “possible” using Tuberculosis Meningitis International Research Consortium criteria, in four African countries: Ivory Coast, Madagascar, Uganda, and South Africa. The primary outcome is all-cause death between inclusion and week 40. Discussion The INTENSE-TBM trial represents a key opportunity to enhance TBM treatment with widely available existing drugs notably in high-incidence settings of both TB and HIV. The trial design is pragmatic and the results will permit early and effective applications in TBM patient care, in both HIV and TB high-incidence countries. Trial registration ClinicalTrials.gov NCT04145258. Registered on October 30, 2019.